2022
DOI: 10.1007/s00068-022-01937-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the evidence on the impact of pre-operative direct oral anticoagulants on patient health outcomes after hip fracture surgery: rapid systematic review

Abstract: Purpose To synthesise the evidence on the impact of pre-operative direct oral anticoagulants (DOACs) on health outcomes for patients who sustain a hip fracture. Method A rapid systematic review of three databases (MEDLINE, Embase and Scopus) for English-language articles from January 2000 to August 2021 was conducted. Abstracts and full text were screened by two reviewers and articles were critically appraised. Data synthesis was undertaken to summarise he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Mitchell et al in their systematic review of 21 articles noted 18.2% of DOAC users having increased blood transfusions, 40% of users had increased length of stay whilst there was no difference in overall blood loss, postoperative complication rates, stroke or mortality rates compared to the control group. 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitchell et al in their systematic review of 21 articles noted 18.2% of DOAC users having increased blood transfusions, 40% of users had increased length of stay whilst there was no difference in overall blood loss, postoperative complication rates, stroke or mortality rates compared to the control group. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al in their systematic review of 21 articles noted 18.2% of DOAC users having increased blood transfusions, 40% of users had increased length of stay whilst there was no difference in overall blood loss, postoperative complication rates, stroke or mortality rates compared to the control group. 11 Studies have been performed assessing DOAC patient's outcomes in the context of early surgery. Mullins et al in their retrospective study reported that 87.3% of the DOAC patients had an operation within 36 h and their results demonstrated no statistically significant increase in transfusions or mortality differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some older adults taking a DOAC, a delay in performing hip fracture surgery to allow medical optimisation may be necessary to reduce intra-and postoperative blood loss [26] and to deliver safe regional anaesthesia [27]. However, currently, there is an absence of consensus regarding the management of patients with a hip fracture taking DOACs [3,22,[28][29][30], with conflicting evidence as to whether delaying surgery provides a health benefit [31]. The hip fracture and DOAC working group, informed by systematic reviews [31,32], literature reviews [28,29] and related clinical practice guidelines [1,3,5,33], developed a core set of 10 themes and questions regarding the management of patients with a hip fracture taking DOACs (online Supporting Information Appendix S1, Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…For some older adults taking a DOAC, a delay in performing hip fracture surgery to allow medical optimisation may be necessary to reduce intra‐ and postoperative blood loss [26] and to deliver safe regional anaesthesia [27]. However, currently, there is an absence of consensus regarding the management of patients with a hip fracture taking DOACs [3, 22, 28–30], with conflicting evidence as to whether delaying surgery provides a health benefit [31].…”
Section: Introductionmentioning
confidence: 99%